Correction: On-chip polyelectrolyte coating onto magnetic droplets – towards continuous flow assembly of drug delivery capsules. Issue 22 (31st October 2017) - Alorabi, Ali Q.; Tarn, Mark D.; Gómez-Pastora, Jenifer; Bringas, Eugenio; Ortiz, Inmaculada; Paunov, Vesselin N.; Pamme, Nicole
Abstract : Correction for 'On-chip polyelectrolyte coating onto magnetic droplets – towards continuous flow assembly of drug delivery capsules' by Ali Q. Alorabi et al., Lab Chip, 2017, DOI: 10.1039/c7lc00918f.